The degree to which kindergarten managers practice the skills of managerial creativity from the point of view of teachers (Field study in the city of Tartus) (Journal of Hama University, 2024)
The research sample consisted of (201) kindergarten teachers in the city of Tartus according to the research variables (scientific qualification, teaching experience), and to achieve this goal, the analytical descriptive curriculum was relied on, and a questionnaire of administrative creativity skills included four axes (originality skill, fluency skill, flexibility skill, sensitivity to problems skill), which was prepared by the researcher, after verifying her honesty and consistency, the results came as follows:The degree to which kindergarten managers practice the skills of managerial creativity from the point of view of teachers is average, with an arithmetic mean (3.03), and a standard deviation (0.507).There are no statistically significant differences at the level of significance (0.05) between the average scores of kindergarten teachers ' answers to the questionnaire of managerial creativity skills depending on the academic qualification variable.The presence of statistically significant differences between the average scores of kindergarten teachers ' answers to the questionnaire of managerial creativity skills depending on the variable of teaching experience and in favor of more than 10 years.The current research, in light of the findings, suggested the need to provide training courses and workshops for kindergarten managers to develop their administrative creativity skills, and to provide appropriate administrative support to managers wishing to apply new and innovative administrative ideas, in addition to providing them with the necessary tools to apply administrative creativity skills.
Keywords: managerial creativity skills